Eimeria tenella Translation Initiation Factor eIF-5A That Interacts With Calcium-Dependent Protein Kinase 4 Is Involved in Host Cell Invasion - Liang, Shanshan; Dong, Hui; Zhu, Shunhai; Zhao, Qiping; Huang, Bing; Yu, Yu; Wang, Qingjie; Wang, Haixia; Yu, Shuilan; Han, Hongyu (Frontiers in Cellular and Infection Microbiology, 2021)
Eimeria are apicomplexan protozoan, and calcium-dependent protein kinases (CDPKs) are effector molecules in calcium signaling pathways, which control important physiological processes such as gliding motility, reproduction, and host cell invasion. CDPKs are found in plants, green algae, and ciliates. Given that CDPKs are not found in the host, studying the functions of CDPKs in Eimeria and their role in calcium signaling may serve as the basis for developing new therapeutic drugs and vaccines. To assess the function of CDPK4 of Eimeria tenella (EtCDPK4), a putative interactor, translation initiation factor eIF-5A of E. tenella (EteIF-5A), was screened by co-immunoprecipitation (co-IP) and His pull-down assays and analyzed by mass spectrometry. The interaction between EteIF-5A and EtCDPK4 was determined by bimolecular fluorescence complementation (BiFC), GST pull-down, and co-IP. The molecular characteristics of EteIF-5A were analyzed. Quantitative real-time polymerase chain reaction and western blotting were used to determine the transcription and translation levels of EteIF-5A in different developmental stages of E. tenella. The results showed that the level of EteIF-5A mRNA transcription was highest in second-generation merozoites, and the protein expression level was highest in unsporulated oocysts. Indirect immunofluorescence showed that EteIF-5A was found throughout the cytoplasm of sporozoites, but not in the refractile body. As the invasion of DF-1 cells progressed, EteIF-5A fluorescence intensity increased in trophozoites, decreased in immature schizonts, and increased in mature schizonts. The secretion assay results analysed by western blotting using staurosporine indicated that EteIF-5A was a secreted protein but not from micronemes. The results of invasion inhibition assays showed that rabbit anti-rEteIF-5A polyclonal antibodies effectively inhibited cell invasion by sporozoites, with an inhibition rate of 48%.